Effect of Difference Tropical Fibrous Feeds on Feed Intake and Digestibility in Swamps Buffaloes Compared to Ongole Cattle - Widyobroto, BP; Budhi, SPS (ANIMAL PRODUCTION, 2010)
This research was aimed to examine the effect of difference fibrous feeds on feed intake and digestibility in swamps buffaloes compared to ongoles cattles. Twelve ongole and twelve buffaloes were used in in vivo digestibility. Ten feeds were used in this experiment, namely Peanut Haulm (PH), King Grass (KG), Corn stover (CS), Elephan Grass (EG), Rice Straw (RS), Soja Straw (SS), Corn Straw (CST), Glyricidea (Gli), and Caliandra (Cal).  The observed variabels were intake of DM, OM, CP, NDF. The results showed that DM and OM intakes were significantly influenced by feed stuffs origin ranged from the lowest (Gli) of 29.55 g DMI/kg0.75 to the highest (CS) of 94.88 g/kg0.75. OM intake of buffaloes was higher than that of ongole cattle supported by organic matter (OM) digestibility data (61.51 vs 59.51).  The digestibility of nutrient was significantly influenced by feed stuffs origin. OM digestibility of SS were lowest while the highest were CST of 54.56 and 71.66% respectively. Digestibility of CP  was also significantly  influenced by feed stuffs origin. The lowest Digestible Crude Protein  was CST and the highest was PH of 44.10 and 67.99% respectively. The digestibility of NDF and ADF were significantly influenced by feed stuffs. The lowest NDF and ADF digestibilities were Cal of 40.84 and 33.19% and the highest digestibility of NDF and ADF were CST of 68.53 and 63.57%.  It can be concluded that there were an important variation of feed compositions and digestibility of fibrous feeds. Buffalo were better than cattle on capacity of ingestion and utilization of fibrous feed. (Animal Production 12(2): 86-90 (2010)Key Words: fibrous feeds, intake, digestibility, ongole cattle, buffaloes